Additional file 8 of ELOVL gene family plays a virtual role in response to breeding selection and lipid deposition in different tissues in chicken (Gallus gallus) - Dandan Wang; Xinyan Li; Panpan Zhang; Yuzhu Cao; Ke Zhang; Panpan Qin; Yulong Guo; Zhuanjian Li; Yadong Tian; Xiangtao Kang; Xiaojun Liu; Hong Li (figshare, 2022)
Additional file 8: Table S6. All genomic SNPs in gene body and 2 kb promoter of ELOVL gene family used for PCA analysis.
Keywords: Genetics